P23 TIMING OF EJECTION FRACTION REASSESSMENT AFTER SACUBITRIL–VALSARTAN INITIATION FOR INDICATION TO DEFIBRILLATOR IMPLANTATION. A SINGLE CENTER EXPERIENCE. (18th May 2022) - Leci, E; Carinci, V; Bugani, G; Greco, C; D'Angelo, C; Pecoraro, A; Casella, G
Abstract: Background: Sacubitril/Valsartan (SV) has been validated for heart failure (HF) with reduced ejection fraction (EF) treatment. SV is effective on hard end–points as well as symptoms and heart remodeling. Present guidelines reccomend at least 3 month of optimized medical therapy (OMT). However, the best timing of EF assessment after SV initiation in order to proceed with defibrillator (ICD) implantation, is still unknown. Purpose: Evaluate timing of improvement of EF after SV initiation in patients (pts) with systolic HF, candidates to primary prevention ICD implantation. Methods: From 1 of february 2018, we evaluated retrospectively clinical and echocardiographic data of all consecutive pts with EF < 35% treated with SV and candidates to primary prevention ICD implantation. We evaluated clinical and echo follow up (Fup). Results have been analyzed with paired T–test. Results: The study involved 95 pts (mean age 67±10 years, 70% male, ischaemic etiology 48%). Mean EF at enrollment was 30 ± 5% (ED vol 90 ±23 ml/m2; ES vol 62 ± 19 ml/m2, severe MR 23%) and NYHA III–IV 50%. In 58% pts reached the target dose of SV (97/103 mg bid). After a mean Fup of 6 months, mean EF of the study population increased to 37±7% (ED vol 80±19 ml/m2, ES vol 51±17 ml/m2, severe MR 5%, p < 0.001), and NYHA III–IV decreased to 8% (p = 0.01). Interestingly, thirty–one pts (32%) had their first Fup within 3 months and showed already an improvement [meanEF 28±5% to 35±6%; ΔEF 7±6%; NYHA III–IV 10 %]. Moreover, 49 pts (51%) had last Fup echo after 1 year (mean 13±6 months) and showed a further EF improvement (meanEF 41±8%; ΔEF 12±9%; p < 0.001).Sixteen pt (16%) underwent ICD (62%) or CRT–D (38%) implantation after 3±2 months of treatment and excluded from further FUP analysis. More favorable effects of treatment with SV were more evident in patient with non–ischaemic etiology of heart failure. Conclusions: After SV initiation in systolic HF, favourable heart remodeling is clearly evident at 6 months FUP, but could be already observed after 3 months . These findings need to be validated from larger trials but suggest that the best timing of EF reassessment to decide for primary prevention ICD is likely between 3 and 6 months after SV initiation. However decision must be taken following close and individualized FUP for every patient, based on clinical characteristics and response to OMT.